PEMBELAJARAN SASTRA SEBAGAI SALAH SATU WUJUD IMPLEMENTASI PENDIDIKAN BERKARAKTER - Yosi Abdian Tindaon (Universitas Negeri Medan, 2012)
ABSTACT Character education is an effort for the student’s better character building. In this time, the discourse about character education was preferred in educational sector. This was caused by the reality that now a days the humanity sensitivity and the sensitivity of about the surrounding phenomenon become worse. The literature teaching which integrated with character education is one of the smart solution to invest early the character values for students. Through literature, since the early the students can do the feeling cultivation, mind cultivation, and spiritual cultivation frequently till undirectly the students have the good behaviors and habbits. The literature teaching direcly or indirectly will help the students to improve their knowledge about the tradition in human live, increase their sensitivity to the personal and society problems, even increase the students knowledge about the science and technology concept. Keywods: character education, literature teaching